2012
DOI: 10.1097/qco.0b013e32835a0d1a
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to achieve a target of zero central line associated bloodstream infections?

Abstract: A zero CLABSI rate should be the target only for ICU populations having CVCs with a dwell time of 1-9 days following aseptic insertion. Additional measures should be reserved for patients with expected longer dwell time. Refinement and validation of surveillance methodology is required before target CLABSI rates can be proposed for non-ICU populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 80 publications
0
21
0
2
Order By: Relevance
“…25 More important seems to be the dwell time with a device exposition. 23,26 It results in a median of 11 days for CVC, 9 days for MV and 12 days for urinary catheter (UC).…”
Section: Discussionmentioning
confidence: 99%
“…25 More important seems to be the dwell time with a device exposition. 23,26 It results in a median of 11 days for CVC, 9 days for MV and 12 days for urinary catheter (UC).…”
Section: Discussionmentioning
confidence: 99%
“…There are no current benchmarked targets for clinicians to compare their current rates of CVAD failure and complications, with the exception of CVAD-associated BSI in the ICU. 128,129 Quality improvement studies have previously demonstrated a marked reduction in complication rates associated with CVAD in pediatrics and neonates, indicating that complication rates depend on the care provided by multidisciplinary clinicians. [130][131][132] Previous international focus on the prevention of CVAD complications from organizations such as the World Health Organization and the Centers for Disease Control and Prevention has been solely on CVAD-associated BSI, and generally in the ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…A study by McLaws et al showed that patients with a central venous line with prolonged hospital stays were associated with a higher infection rates (20). Therefore, we agree with Worth et al that a zero rate of infection should be limited to ICU patients with short-term central venous catheters and this is not always applicable to high-risk groups with long stays in hospital (21).…”
Section: Discussionmentioning
confidence: 36%